2022
DOI: 10.3389/fpls.2021.804600
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Profiling of DUF221 Gene Family Provides New Insights Into Abiotic Stress Responses in Potato

Abstract: The domain of the unknown function 221 proteins regulate several processes in plants, including development, growth, hormone transduction mechanism, and abiotic stress response. Therefore, a comprehensive analysis of the potato genome was conducted to identify the deafness-dystonia peptide (DDP) proteins’ role in potatoes. In the present study, we performed a genome-wide analysis of the potato domain of the unknown function 221 (DUF221) genes, including phylogenetic inferences, chromosomal locations, gene dupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Moreover, nearly all CsOSCAs had a consistent conserved motif arrangement ( Figure 2 A). Gene structure analysis revealed that the CsOSCA genes had clade-specific exon-intron patterns, and some genes had similar exon/intron structures but different sequence lengths ( Figure 2 B), which is also the case in rice [ 15 ], G. hirsutum [ 16 ], and potato [ 30 ]. The highly conserved evolutionary relationship, conserved motif and exon-intron arrangement of the OSCA genes indicated that the members in the same group probably have conserved functions after gene duplication and phylogenetic diversification events [ 14 ].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, nearly all CsOSCAs had a consistent conserved motif arrangement ( Figure 2 A). Gene structure analysis revealed that the CsOSCA genes had clade-specific exon-intron patterns, and some genes had similar exon/intron structures but different sequence lengths ( Figure 2 B), which is also the case in rice [ 15 ], G. hirsutum [ 16 ], and potato [ 30 ]. The highly conserved evolutionary relationship, conserved motif and exon-intron arrangement of the OSCA genes indicated that the members in the same group probably have conserved functions after gene duplication and phylogenetic diversification events [ 14 ].…”
Section: Discussionmentioning
confidence: 90%
“…In this study, various stress- and hormone-responsive cis -elements that play essential roles in stress response through regulation of stress-responsive genes were found in the promoter regions of CsOSCA genes ( Figure 4 ), implying the possible roles of CsOSCA genes in stress response. Multiple cis -elements involved in multiple stress responses (hormones and abiotic stresses) have also been identified in the promoters of OSCA genes in other plant species, such as G. hirsutum [ 16 ], maize [ 18 ], soybean [ 9 ], tomato [ 28 ], and potato [ 30 ]. We then examined the transcript levels of seven selected CsOSCA genes under three osmotic-related abiotic stresses including drought, salt and ABA by qRT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Expression pro ling of ATDUF4228 genes under abiotic stresses such as osmotic, salt, and cold stress suggested that some ATDUF4228 genes may be involved in plant resistance pathways against abiotic stresses [16]. Furthermore, StDDP5 and StDDP7, both of which belong to the DUF221 gene family, exhibited high expression against heat and salt stress, respectively, in potatoes [17].…”
Section: Introductionmentioning
confidence: 99%
“…Expression profiling of ATDUF4228 genes under abiotic stresses such as osmotic, salt, and cold stress suggested that some ATDUF4228 genes may be involved in plant resistance pathways against abiotic stresses [16]. Furthermore, StDDP5 and StDDP7, both of which belong to the DUF221 gene family, exhibited high expression against heat and salt stress, respectively, in potatoes [17].…”
Section: Introductionmentioning
confidence: 99%